EXT1 as an Independent Prognostic Biomarker in Breast Cancer: Its Correlation with Immune Infiltration and Clinicopathological Parameters - Amira Hossny; Hatem A. F. M. Hassan; Sherif Ashraf Fahmy; Hazem Abdelazim; Mahmoud Mohamed Kamel; Ahmed H. Osman; Sherif Abdelaziz Ibrahim (Immuno)
Exostosin 1 (EXT1) encodes a type II transmembrane glycosyltransferase residing in the endoplasmic reticulum and plays an essential role in the elongation of heparan sulfate chain biosynthesis. Additionally, EXT1 may act as an oncogene that could promote cell proliferation as well as cancer cell metastasis. Herein, we investigated EXT1’s expression pattern and prognostic value in breast cancer, along with its immunological implications. Immunohistochemical staining of EXT1 was assessed in 85 breast cancer patients. Patients were categorized into molecular subtypes, namely luminal A, luminal B, and human epidermal growth factor receptor 2 (HER2), along with triple-negative breast cancer (TNBC). Correlations of EXT1 immunostaining with clinicopathological parameters were evaluated. Furthermore, the correlations of EXT1 expression with tumor immune infiltration and immune cell surface markers were assessed using TIMER. Moreover, survival analysis was conducted to reveal EXT1’s prognostic value. EXT1 expression was markedly associated with the status of the estrogen receptor (ER), molecular subtypes, and recurrence status. In addition, high levels of EXT1 expression were associated with worse overall survival (OS) and relapse-free survival (RFS). Analysis of immune infiltration indicated that EXT1 expression was positively correlated with dendritic cells (DCs), macrophages, neutrophils, CD4+ T cells, and CD8+ T cells, although it showed a negative correlation with the tumor purity. Overall, this study suggests that the elevated EXT1 expression, particularly in TNBC, has a positive correlation with poor prognosis and with immune-infiltrated cells in breast cancer. Therefore, it may emerge as an independent prognostic biomarker, immunological marker, and potential future therapeutic target for the most aggressive TNBC subtype.